Clinical Spectrum and Outcome of Empyema in Nepalese Children - Bhatta, NK; Singh, AP; Kalakheti, B; Khanal, B; Shrestha, P; Singh, R (Journal of Nepal Paediatric Society, 2008)
Keywords: Empyema; chest tube drainage, decortication DOI = 10.3126/jnps.v28i2.1387 J. Nepal Paediatr. Soc. Vol.28(2) 2008 p.49-51